2016
DOI: 10.1007/s00405-016-4154-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic aspects in the treatment of juvenile nasopharyngeal carcinoma: a systematic review

Abstract: To systematically review and discuss the published data about treatments and outcomes for children and adolescents affected by nasopharyngeal carcinoma. In April 2015, an appropriate string was run on PubMed to retrieve all relevant articles. A cross-check was performed by two of the authors on abstracts and full-text articles found using the selected inclusion and exclusion criteria. A meta-analysis concerning the rate of reported disease-free survival and overall survival was performed. Fifteen studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…A previous study has suggested that future perspectives for clinical research should include prospective and observational cohort studies, which may assess the effects of different risk factors in the development of NPC and the effectiveness of investigational treatments (5). Although previous studies have investigated numerous anticancer drugs including nimotuzumab, oxaliplatin and gemcitabine for the treatment of NPC (6)(7)(8)(9), the therapeutic outcomes are not encouraging so far. Therefore, exploring efficient anticancer agents and the potential underlying molecular mechanisms of cellular migration and metastasis in NPC are required.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has suggested that future perspectives for clinical research should include prospective and observational cohort studies, which may assess the effects of different risk factors in the development of NPC and the effectiveness of investigational treatments (5). Although previous studies have investigated numerous anticancer drugs including nimotuzumab, oxaliplatin and gemcitabine for the treatment of NPC (6)(7)(8)(9), the therapeutic outcomes are not encouraging so far. Therefore, exploring efficient anticancer agents and the potential underlying molecular mechanisms of cellular migration and metastasis in NPC are required.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the preferred treatment consists of a combined regimen of radiation therapy and chemotherapy. It has been demonstrated that in children, neoadjuvant chemotherapy can be used to achieve tumor reduction, improve local tumor control, and treat systemic micrometastases-thus, lowering radiation therapy doses (71). In addition to chemotherapy, interferon-β is used, as it appears to have antitumor effects in patients with Epstein-Barr virus-positive NPC (71,72).…”
Section: Nasopharyngeal Carcinomamentioning
confidence: 99%
“…Several clinical features, including age, gender, stage, RT technique, RT dose, and response to chemotherapy can predict the prognosis in children with NPC (5)(6)(7)(8)(9)(10). However, the variable outcomes of patients within heterogeneous subgroups suggest that clinical features alone cannot precisely predict the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%